2022
DOI: 10.3390/antibiotics11080999
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Enteropathogenic Escherichia coli Isolated from Diarrhoeic Calves, Milk, and Workers in Dairy Farms: A Potential Public Health Risk

Abstract: Enteropathogenic Escherichia coli (EPEC) is a leading cause of diarrhoeagenic diseases in humans and cattle worldwide. The emergence of multidrug-resistant (MDR) EPEC from cattle sources is a public health concern. A total of 240 samples (75 diarrhoeic calves, 150 milk samples, and 15 workers) were examined for prevalence of EPEC in three dairy farms in Egypt. Antimicrobial resistance (AMR) traits were determined by antibiogram and polymerase chain reaction (PCR) detection of β-lactamase-encoding genes, plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…No. K001-1KT; HiMedia, Maharashtra, India) ( 9 , 27 ). Biochemical analysis confirmed the presence of pure E. coli colonies by means of triple sugar iron agar (TSIA) (cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No. K001-1KT; HiMedia, Maharashtra, India) ( 9 , 27 ). Biochemical analysis confirmed the presence of pure E. coli colonies by means of triple sugar iron agar (TSIA) (cat.…”
Section: Methodsmentioning
confidence: 99%
“…The spread and transfer of E. coli with ESBLs can take place through food supply chains, contaminated faeces, contaminated water, and hazardous waste. Clinical symptoms or disorders caused by E. coli can appear as urinary tract infections, septic shock, and diarrhoeal illnesses ( 9 , 18 ). Mastitis is a condition that can affect lactating animals and has been linked to E. coli infections ( 3 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Egypt, a study of Enteropathogenic E. coli (EPEC) either isolated from diarrhoeic calves (17/75), milk (8/150), or workers (3/15) in dairy farms has reported that all EPEC (100%) isolates were MDR, with high resistance rates observed in ampicillin (100%), tetracycline (89.3%), cefazolin (71%), and ciprofloxacin (64.3%) [25].…”
Section: Current Situation Of E Coli Antibiotic Resistance In Food-pr...mentioning
confidence: 99%
“…Manifestations of disease in animals caused by these bacteria result in mastitis (Aslam et al 2021). Other diseases are digestive diseases in animals and humans which are often caused by E. coli (EPEC) strains (Eldesoukey et al 2022), urinary traTable 1ct diseases and septic shock in humans (Mueller and Tainer 2022).…”
Section: Introductionmentioning
confidence: 99%